2018
DOI: 10.1111/ijac.13136
|View full text |Cite
|
Sign up to set email alerts
|

Effective dielectric loss (tan δ) reduction of CaCu3Ti4O12 (CCTO) via various addition of glasses

Abstract: Addition of various glasses has successfully reduced tan δ of CCTO-based ceramics. Less amounts (0-1.0 wt%) of glasses (BaO-SrO-Nb 2 O 5 -B 2 O 3 -SiO 2 [BSNBS] and SrO-B 2 O 3 -SiO 2 [SBS], respectively) were added into pure CCTO and sintered at 1040°C for 10 hours. The phase formation and microstructure of each sample were characterized using X-ray diffraction and scanning electron microscopy, respectively. The dielectric behavior of the samples was measured at 1 MHz. The addition of BSNBS and SBS glasses (≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Higher amounts of BSNBS glass contributed to the smaller grain size of CCTO. The glass addition seemed to have segregated CuO at the grain boundaries and restricted the CCTO’s grain growth as detected by EDX and XRD analyses reported in our previous work 30 . The presence of both glassy and CuO phases cannot be clearly seen on the surface of each sample but was detected by EDX analysis on the sample cross‐section.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…Higher amounts of BSNBS glass contributed to the smaller grain size of CCTO. The glass addition seemed to have segregated CuO at the grain boundaries and restricted the CCTO’s grain growth as detected by EDX and XRD analyses reported in our previous work 30 . The presence of both glassy and CuO phases cannot be clearly seen on the surface of each sample but was detected by EDX analysis on the sample cross‐section.…”
Section: Resultssupporting
confidence: 57%
“…The presence of both glassy and CuO phases cannot be clearly seen on the surface of each sample but was detected by EDX analysis on the sample cross‐section. The formation of CuO phase alongside major CCTO phase has also been proven by XRD analysis 30 . It is observed that the major peaks belong to CCTO in all composites since the maximum amount of each glass added was only 1 wt%.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…One of the most interesting approaches used to decrease the tan δ is by incorporating glass ceramics, for instance, SiO 2 in a dielectric material. [ 29 ] High electrical resistance (≈15 MV cm −1 ) [ 30 ] coupled with low tan δ (3.8 × 10 −4 ) of SiO 2 reduces tan δ , thereby improving dielectric properties. However, such devices based on glass blending mandate specialized insulating materials to shield from electrical discharge, which increases the overall production cost.…”
Section: Introductionmentioning
confidence: 99%